Study on (r, s)-generalised transformation graphs, a novel perspective based on transformation graphs - Ali Parvez; Baby Annmaria; Xavier D. Antony; Theertha Nair A.; Ali Haidar; Kirmani Syed Ajaz K. (Main Group Metal Chemistry)
For a graph Q=(V,E){\mathbb{Q}}=\left({\mathbb{V}},{\mathbb{E}}), the transformation graph are defined as graphs with vertex set being V(Q)∪E(Q){\mathbb{V}}\left({\mathbb{Q}})\cup {\mathbb{E}}\left({\mathbb{Q}}) and edge set is described following certain conditions. In comparison with the structural descriptor of the original graph Q{\mathbb{Q}}, the topological descriptor of its transformation graphs displays distinct characteristics related to the structure. Thus, a compound’s transformation graph descriptors can be used to model a variety of structural features of the underlying molecular structure and initiate a structural analysis. In this work, the concept of transformation graphs is extended giving rise to a novel class of graphs, the (r,s)\left(r,s)-generalised transformation graphs, whose vertex set is union of rr copies of V(Q){\mathbb{V}}\left({\mathbb{Q}}), and ss copies of E(Q){\mathbb{E}}\left({\mathbb{Q}}), where r,s∈Nr,s\in N, and the edge set are defined under certain conditions. Furthermore, this class of graphs is analysed with the help of first Zagreb index. Mainly, there are eight transformation graphs based on the criteria for edge set, but under the concept of (r,s)\left(r,s)-generalised transformation graphs, infinite number of graphs can be described and analysed.